Apoptotic volume decrease (AVD) in A549 cells exposed to water-soluble fraction of particulate matter (PM10) - Giordano, M. E.; Udayan, G.; Guascito, M. R.; De Bartolomeo, A. R.; Carlino, A.; Conte, M.; Contini, D.; Lionetto, M. G. (Frontiers in Physiology, 2023)
The eExposure to atmospheric particulate matter (PM) is recognized as a human health risk factor of great concern. The aim of the present work wasThe present work aimed to study the cellular mechanisms underlying cytotoxic effects of airborne particulate matter < 10 µm in size (PM10), sampled in an urban background site from January to May 2020, on A549 cells. In particular, the study addressed if PM10 exposure can be a main factor in the induction of the Apoptotic Volume Decrease (AVD), which is one of the first events of apoptosis, and if the generation of intracellular oxidative stress can be involved in the PM10 induction of apoptosis in A549 cells. focusing on one of the earliest events of apoptosis, the Apoptotic Volume Decrease (AVD).The cytotoxicity of PM10 samples was measured by MTT test on cells exposed for 24h to the PM10 aqueous extracts, cell volume changes were monitored by morphometric analysis of the cells, apoptosis appearance was detected by annexin V and the induction of intracellular oxidative stress was evaluated by the ROS sensitive CM-H2DCFDA fluorescent probe.The results showed cytotoxic effects ascribable to apoptotic death in A549 cells exposed for 24h to aqueous extracts of airborne winter PM10 samples characterized by high PM10 value and organic carbon content. The detected reduced cell viability in winter samples ranged from 55% to 100%. Normotonic cell volume reduction (ranging from about 60% to 30 % cell volume decrease) after PM10 exposure was already detectable after the first 30 min clearly indicating the ability of PM10, mainly arising from biomass burning, to induce Apoptotic Volume Decrease (AVD) in A549 cells.AVD was prevented by the pre-treatment with 0.5 mM SITS indicating the activation of Cl -efflux presumably through the activation of VRAC channels. The exposure of A549 cells to PM10 aqueous extracts was able to induce intracellular oxidative stress detected by using the ROSsensitive probe CM-H2DCFDA. The PM10 inducedPM10-induced oxidative stress was statistically significantly correlated with cell viability inhibition and with apoptotic cell shrinkage. It was